Transforming Rehabilitation: Probation practice, architecture and the art of distributions - Tidmarsh, Matt (Criminology & criminal justice, 2021)
This article explores probation practice through the architecture and arrangement of a probation office led by a Community Rehabilitation Company. It presents findings from an ethnographic study of a probation office in a large city, combining observations of the research site with data derived from interviews with 20 members of staff. Drawing on Foucault’s art of distributions, the article highlights how the managerial dynamics of recent decades have filtered into the physicality of the office to influence probation practice. It argues that probation practice under Transforming Rehabilitation can be situated along a managerial continuum, as standardized, computer-based work has become further entrenched within the office.